Assessment of Small-scale Buffalo Milk Dairy Production-A Premise for a Durable Development - Marian MIHAIU; Alexandra LAPUSAN; Romolica MIHAIU; Sorin D. DAN; Carmen JECAN (Notulae Scientia Biologicae, 2012)
Buffalo husbandry is an important source of income for a number of small-scale producers in Romania that is why an assessment of its products quality is much needed for improvement and evaluation of their vulnerability to international competition. In order to ascertain possible developments in the buffalo dairy sector and to broadly identify areas of intervention that favor small-scale dairy producers, the study examined the potential to improve buffalo milk production by evaluating its authenticity and hygienic quality. The methods used involved the molecular testing (PCR-technique) for identifying cow, sheep or goat DNA in the dairy products samples collected from the small-scale producers market. The hygienic quality of these samples was determined through classical microbiology methods, highly developed techniques (Trek System) and PCR for bacterial species confirmation. The results showed that a high percent (65%), from the products found were adulterated with other species milk, mostly cow milk. The most commonly falsified buffalo dairy products were the cheese and the traditional product telemea. The prevalence of the bacterial species identified belonged to Listeria innocua and Listeria welshmeri. The conclusion of this study is the need of a durable development system in this particular dairy chain to improve and assure the authenticity and quality of the small-scale producers products and their reliability for the consumers.